Working Period and CO Exposure Relationship with Changes Levels COHb of Bus Station Officer - Rachmawati, Siti; Suryadi, Iwan; Safitri, Ferlin Ayu; Firmansyah, Fathoni (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Carbon monoxide inhaled into the lungs will enter the blood circulation and inhibit the entry of oxygen needed by the body. This gas combines with hemoglobin to form carboxyhemoglobin (COHb). The increase in COHb in the blood will inhibit the function of oxygen transportation and will affect the health of workers. This study aims to determine the risk factors for increasing COHb in Tirtonadi Bus Station Surakarta officers. The research method used analytic observational with a cross-sectional design. The research population was 110 respondents with a purposive sampling technique to get a research sample of 43 respondents. CO levels in the environment were measured by a CO meter, while COHb levels were measured by a spectrophotometer. The research data were analyzed using Spearman rank. Statistical correlation test showed a significant relationship between CO levels in the environment and COHb levels, p-value = 0.000 and r-value = 0.897, and no significant relationship between length of work and COHb levels with p-value = 0.285 and r-value = - 0.167. CO in the environment is related to the COHb level of traffic security officers at Tirtonadi Bus Station Surakarta, and the length of work is not related to the COHb level of traffic security officers at Tirtonadi Bus Station Surakarta.